Partisipasi Politik Pensiunan TNI-AD Pada Pilpres 2024 : (Studi Kasus Pensiunan TNI Yang Baru Menggunakan Hak Pilih dikota Kupang) - Muhammad F. Wiratama; Ananias Riyoan Philips Jacob; Frans B. Ricky Humau (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This study aims to analyze the relationship between the sociological, psychological, and rational behaviors of retired members of the Indonesian Army (TNI AD) towards their presidential choices in the 2024 general elections in Kupang City. By focusing on these three behavioral aspects, the research seeks to uncover how these factors influence the political decisions of retired TNI AD personnel when determining their presidential candidate preferences. The research employs a quantitative approach, collecting data through questionnaires distributed to retired TNI AD respondents. Data analysis is conducted using the chi-square technique to evaluate the significant relationships between the sociological, psychological, and rational behaviors and presidential choices. The study involves a sample of respondents representing the retired TNI AD population in Kupang City. The analysis results indicate a significant relationship between the sociological, psychological, and rational behaviors of retired TNI AD personnel and their presidential choices in the 2024 elections. Sociological behavior, which includes ethnic identity and social involvement, significantly affects political preferences, while psychological behavior related to emotional closeness to supporting parties also shows a noteworthy impact. Additionally, rational behavior, which assesses the alignment of candidates' programs with voters' needs, influences decisions, highlighting the importance of these three aspects in the electoral choices of retired TNI AD personnel.